2002
DOI: 10.1097/00005768-200208000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Moderate to vigorous physical activity and risk of upper-respiratory tract infection

Abstract: These data support the hypothesis that moderate levels of physical activity are associated with a reduced risk for URTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
166
0
11

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(189 citation statements)
references
References 23 publications
12
166
0
11
Order By: Relevance
“…Nevertheless, small variations in the scoring were taken into account by using a continuous grading scale for intakes close to NNR cut-offs. Our results on physical activity and URTI are supported by previous studies which have suggested a protective association on URTI of moderate levels of physical activity (28) , possibly mediated by a higher circulating number of natural killer cells found in resting athletes (29) . Although we cannot rule out a potential effect of reverse causality, to minimize this possibility we assessed exposure before outcome (i.e.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, small variations in the scoring were taken into account by using a continuous grading scale for intakes close to NNR cut-offs. Our results on physical activity and URTI are supported by previous studies which have suggested a protective association on URTI of moderate levels of physical activity (28) , possibly mediated by a higher circulating number of natural killer cells found in resting athletes (29) . Although we cannot rule out a potential effect of reverse causality, to minimize this possibility we assessed exposure before outcome (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…The FFQ does not assess the entire IRR, incidence rate ratio. *IRR for all adherence scores were adjusted for age (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)30-39, 40-49 and 50-60 years), sex, energy intake (in four categories), BMI (low, normal, overweight and obese), weakened immune system (yes/no), asthma (yes/no), perceived stress (below and above median), education level (secondary school or less and university), smoking (daily/less frequent/previous/never) and month (February to May).…”
Section: Discussionmentioning
confidence: 99%
“…The intensity and duration of exercise plays a key role in determining responses to exercise (Fielding et al, 2000;Matthews et al, 2002). In Nieman's ''J-shaped model'' for upper respiratory tract infection it was postulated that exercise could enhance or reduce immunity depending on the frequency, duration, and intensity of the exercise (Nieman, 1994).…”
Section: Cell Defense and Repairmentioning
confidence: 99%
“…A intensidade, a duração e a freqüência do exercício exercem papel chave na determinação das respostas imunológicas, podendo aumentar ou reduzir tal função 1,2 . A prática de atividade física regular realizada em intensidade moderada pode levar à redução na ocorrência de infecções, especialmente do trato respiratório superior (ITRSs) 1 .…”
Section: Introductionunclassified
“…A prática de atividade física regular realizada em intensidade moderada pode levar à redução na ocorrência de infecções, especialmente do trato respiratório superior (ITRSs) 1 .…”
Section: Introductionunclassified